Implementasi E Katalog Terhadap Perkembangan UMKM di Kota Pekanbaru - Ahmad, Annisa (LPPM Universitas Putera Batam, 2024)
The purpose of this study is to analyze the implementation of e-catalog in the procurement of government goods / services and to examine the effect of the implementation of e-catalog in the procurement of government goods / services on Micro, Small and Medium Enterprises (MSMEs). Currently, Indonesia is a developing country with Indonesia's rapid economic growth accompanied by the development of regional autonomy, the government's need for governance is also increasing. This development means the government needs more governance.Government needs for the construction of facilities and infrastructure can be as a provision of public services must be carried out through the process of procurement of goods / services. The research method used is descriptive. The implementation of government goods / services procurement by e catalog will be more open, transparent and efficient by cutting down the process and time in the administration of government goods / services. The implementation of e-catalog in the procurement of government goods / services influences the MSME sector, there are still small-scale industry players who have been the goods / services distribution chain. Through the e-catalog that breaks the distribution chain, it causes the elimination of the role of small service providers that have been part of the distribution chain. The government has encouraged the use of the e catalog system for MSMEs, one of which is the participation of MSMEs in local e catalog products. In the implementation of the use of the e catalog system for MSMEs is still lacking, as evidenced by the still minimal use of the e catalog system by MSMEs because of the limited capital and information related to the use of the e catalog system.